Case Report: Ductal Carcinoma In Situ in the Male Breast - Joshua Chern; Lydia Liao; Raymond Baraldi; Elizabeth Tinney; Karen Hendershott; Pauline Germaine (Case Reports in Radiology)
High-grade ductal carcinoma in situ is incredibly rare in male patients. The prognosis for ductal carcinoma in situ (DCIS) in a male patient is the same as it would be for a female with the same stage disease; therefore, early recognition and diagnosis are of the utmost importance. We present a case of a male with unilateral invasive ductal carcinoma who was diagnosed with DCIS in the contralateral breast. The DCIS presented as microcalcifications on mammography and was found to be biopsy proven grade 3 papillary DCIS. This case also illustrates the importance of family history and risk factors, all of which need to be evaluated in any male presenting with a breast mass or nipple discharge.